Norte Bienal: uma história da arte no interior do Ceará - Ferreira, Antonio Edivaldo (2023)
This study represents an exploration of the memories that constitute the recent history of art in Ceará’s inland cities. It focuses on the production of visual arts in the state, originating from Sobral, exploring through remembrance the narratives of its main collective exhibitions that occurred between 2000 and 2013, as well as the five editions of the Norte Bienal; the subject of this research, held in the municipality between 2014 and 2022. Norte Bienal is a project dedicated to cataloging, fostering, and disseminating visual arts produced in Ceará’s inland cities, with its formative, artistic, and social activities predominantly carried out in Sobral. To tell this story, some routes, contexts and important events were revisited, such as the Sobral Salon of Contemporary Art, as a way to acquaint the reader with the cultural landscape of Sobral before the project's initiation. Authors such as Sonia Salcedo del Castillo (2014), Glória Ferreira (2006, 2010), and Gilmar de Carvalho (2010), among others, played a fundamental role in shaping the narrative of these exhibitions and their ramifications, essential for recounting the history of art in Ceará. The main objective of this proposal is to document how Norte Bienal contributed to making the art produced in Ceará’s inland cities into something that is “simultaneously an event, documentation, and historical reference” (FERREIRA, 2006, p. 138). The creation of this document aims to bring visibility to the artists and the artistic production that exists in this territory, highlighting its importance for the art history of Ceará. To achieve these goals, this study employed interviews, consultations of photographic and audiovisual archives, catalogs, newspaper articles, and records of statements made by artists and project collaborators.